Testis and brown adipose tissue xenografts from yellowish myotis (Myotis levis) - Talita De Oliveira Farias; André Felipe Almeida Figueiredo; Natalia Teixeira Wnuk; Sônia Aparecida Talamoni; Guilherme Mattos Jardim Costa (Bioscientifica, 2022)
Yellowish myotis present a seasonal reproduction, influenced by rainfall distribution, in which the testis mass, germ cell composition, and brown adipose tissue (B.A.T.) mass change along the reproductive stages. In the present study, tissue xenografts were performed in immunodeficient mice to investigate spermatogenesis development in a stable endocrine milieu and the possible androgenic role of B.A.T. In this study, 41 adult male bats were captured in the Santuário do Caraça, Minas Gerais, Brazil. The gonads and B.A.T. were collected, weighed, and grafted under the mice's back skin. Mice biometric and hormonal data were evaluated after grafting, and the testis grafts and mice gonads were fixed for histological and immunohistochemical analyses. As a result, testis grafts from adult bats presented a continuous germ cell development in all reproductive stages, showing round spermatids in all testis tissues. Furthermore, testis fragments in the Rest stage presented elongating spermatids as the most advanced germ cell type in the seminiferous epithelium after 7 months of grafting. These data indicated that yellowish myotis spermatogenesis could be continued (presenting a constant spermatogonial differentiation) in a stable endocrine milieu, as found in mice. In addition, the best spermatogenic development was achieved when testis fragments were transplanted at their lowest activity (Rest stage). Regarding the B.A.T. grafts, the adipose tissue consumption by mice increased seminal vesicle mass and testosterone serum levels. This data proves that B.A.T. is related to testosterone synthesis, which may be critical in stimulating the differentiation of spermatogonia in yellowish myotis.